2008
DOI: 10.1097/smj.0b013e318181881b
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Vitamin D Deficiency and Insufficiency in Northeast Tennessee

Abstract: Vitamin D deficiency is highly prevalent in all age groups and in both females and males in this population. Clinicians should consider measuring the vitamin D level of all inpatients on a routine basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Mean calcium levels were 2.24 ± < 0.01 mmol/L for men, (α2 = 55.175; p < 0.001). Using generalised estimating equations analysis with odds ratios and adjusting for the covariate of age (Table II), we found that all the years prior to 2010 were associated with higher odds of vitamin D deficiency to Our data indicated that vitamin D deficiency was clearly prevalent in our population -(i) the frequency distribution of (29,32,33) and Denmark, (34) where a high degree of vitamin D deficiency was seen among the populations studied. According to Hirani et al, women were more likely to be vitamin D deficient than men.…”
Section: E Th O Dsmentioning
confidence: 84%
“…Mean calcium levels were 2.24 ± < 0.01 mmol/L for men, (α2 = 55.175; p < 0.001). Using generalised estimating equations analysis with odds ratios and adjusting for the covariate of age (Table II), we found that all the years prior to 2010 were associated with higher odds of vitamin D deficiency to Our data indicated that vitamin D deficiency was clearly prevalent in our population -(i) the frequency distribution of (29,32,33) and Denmark, (34) where a high degree of vitamin D deficiency was seen among the populations studied. According to Hirani et al, women were more likely to be vitamin D deficient than men.…”
Section: E Th O Dsmentioning
confidence: 84%
“…All of the patients had one of the AITD (GD or HT) and Vitamin D deficiencies defined as serum values <20 ng/mL. [171819]…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence suggests that vitamin D is a key regulator of the immune system, 12 and as such, it may play an important role in patient susceptibility to hospital‐acquired infections, 13 including HACDIs 14 . Given that the prevalence of suboptimal levels of 25‐hydroxyvitamin D (25(OH)D) has increased in the general population, 15 19 we performed a 2‐center retrospective cohort study of hospitalized adult patients among whom 25(OH)D was measured within 1 year of hospitalization. Our objective was to test the hypothesis that vitamin D status before hospital admission is associated with the risk of developing HACDIs.…”
Section: Introductionmentioning
confidence: 99%